Non – Vision Based Sensors for Dynamic Hand Gesture Recognition Systems: A Comparative Study - H T, Panduranga; C, Mani. (International Journal of Engineering and Technology, 2018)
Gestures are considered as a type of configuration associated with motion in concerned body part, signifying meaningful information or expressing motion or intending to command and control.Â Wide ranges of sensors working with different technology are available in market.Â Gesture recognition process involves steps like data acquisition from sensor, segmentation, an algorithm for taking gesture data as input, an algorithm to extract parameters and algorithm to classify hand gestures.Â Three - dimensional hand gestures have been widely accepted for advanced applications like creation of virtual world where in users can feel the naturality of interacting or playing a musical instrument without presence of any physical device.Â Techniques for dynamic finger gesture recognition can be classified as visual based and wearable sensor based.Â The purpose of this paper is to compare various non â€“ vision based sensors with different tracking technologies, updating advantages and drawbacks helping investigators and researchers working on this area.Â Â